Towards Analysis and Optimization of Electrospun PVP (Polyvinylpyrrolidone) Nanofibers. (4th May 2020) - Utkarsh,; Hegab, Hussien; Tariq, Muhammad; Syed, Nabeel Ahmed; Rizvi, Ghaus; Pop-Iliev, Remon
Abstract : In this study, the polymeric nanofibers of polyvinylpyrrolidone (PVP) were manufactured using the electrospinning technique. The electrospinning process parameters such as voltage, polymer concentration, rotational speed of the collecting drum, collecting distance, and flow rate were optimized to obtain the minimum fiber diameter for sound absorption applications. The effects of these parameters on the fiber diameter as output responses were investigated by analysis of variance (ANOVA) and Taguchi's array design. Furthermore, a mathematical model was generated using response surface methodology (RSM) to model the electrospinning process. The high voltage and polymer concentration were observed to be the most significant parameters at 95% and 99% confidence level. The average model accuracy of 83.4% was observed for the predictive model of electrospinning which is considered acceptable as it is composed of complete experimental trials of 27 out of 243 runs. The experimental study offers a promising attempt in the open literature to carefully understand the effect of various electrospinning parameters when producing PVP nanofibers.